Family farm: A multidimensional reality - Mărioara Rusu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Family farming plays an important role in food security and sustainable rural development, in both developed and developing countries. If in recent history, Western Europe was based on a strong sector of family farming, for Romania and other former communist countries, it reappeared in the debate after the changes that occurred in the 1990s. (the collapse of the communist regimes). Due to the complexity and heterogeneity of farms all over the world, there is currently no consensus on the definition of family farming: how the family farm is defined varies by country and context. The objective of this paper is to identify family farms in Romania based on accessible parameters, easy to measure. The approached topic required the use of an appropriate methodology, which included both methods of documentary and statistical analysis. The emerged conclusion was that proposing a definition and selecting specific parameters has a significant importance in characterizing and evaluating the importance of family farms, an important step in proposing and implementing dedicated policies.
Keywords: Q12; 330; farm; definitions of family farm; defining parameters; Romania